The Oligomerization of Phosphinoborane by Titanium Complexes1. Issue 19 (10th April 2013) - Thoms, Christine; Marquardt, Christian; Timoshkin, Alexey Y.; Bodensteiner, Michael; Scheer, Manfred
<x xml:space="preserve">Abstract</x> The PB chain gang: The reactions of an acetylene complex of titanocene with the parent phosphinoborane stabilized only by a Lewis base lead to novel phosphinoborane oligomers coordinated by Cp2Ti complex fragments. Depending on the reaction conditions (temperature and stoichiometry), unprecedented oligomeric chains of phosphinoborane are obtained by dehydro‐oligomerization and PP coupling reactions. btmsa = bis(trimethylsilyl)acetylene.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>